2020
DOI: 10.1002/aet2.10525
|View full text |Cite
|
Sign up to set email alerts
|

Using a Simulated Model and Mastery Learning Approach to Teach the Ultrasound‐guided Serratus Anterior Plane Block to Emergency Medicine Residents: A Pilot Study

Abstract: Background:The serratus anterior plane block (SAPB) is a safe, single-injection alternative for pain control in patients with rib fractures. This pilot study aims to teach the ultrasound-guided SAPB to emergency medicine (EM) residents using a mastery learning approach.Methods: A 19-item checklist was created and mastery was determined to be 17 of 19 items correct. This pass score was established using a Mastery Angoff standard-setting exercise with a group of EM experts. Learners participated in baseline test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Prior to this study, a group of emergency physicians at our institution underwent a training session on SAPB augmented by highfidelity simulation. 17 The ability of these physicians to learn the SAPB during a single training session reflects the relative technical ease of this nerve block and suggests that it is feasible for a diverse group of acute care physicians to master. However, given the relative novelty of the procedure, there remains the possibility of operator-dependent block efficacy.…”
Section: Open Accessmentioning
confidence: 99%
“…Prior to this study, a group of emergency physicians at our institution underwent a training session on SAPB augmented by highfidelity simulation. 17 The ability of these physicians to learn the SAPB during a single training session reflects the relative technical ease of this nerve block and suggests that it is feasible for a diverse group of acute care physicians to master. However, given the relative novelty of the procedure, there remains the possibility of operator-dependent block efficacy.…”
Section: Open Accessmentioning
confidence: 99%
“…In total, 16 articles in total were used in this review concluding that the continuous SAPB was found to be favorable to the single injection method when left in the patient for 3 to 5 days. Rider et al 52 conducted a study of 28 emergency medicine residents to test the efficacy of using simulation-based mastery learning to learn how to perform the SAPB. A mastery checklist was created by faculty familiar with the SAPB to judge residents; a score of 17/19 was deemed mastery.…”
Section: Other Invasive Analgesic Proceduresmentioning
confidence: 99%
“…[6][7][8][9][10][11][12] Checklists have previously been proposed for EUS, focused echocardiography by surgical residents, fetal assessment ultrasounds (USs) for obstetrics residents, and abdominal ultrasonography by radiology trainees. 10,[13][14][15][16][17] However, checklists are not widely utilized due partly to remaining gaps in the literature. Prior checklists were often based on local expert opinion at a single institution and lacked reliability and validity evidence.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…Checklists may help guide individualized deliberate practice with mastery learning and better inform competency assessments 6–12 . Checklists have previously been proposed for EUS, focused echocardiography by surgical residents, fetal assessment ultrasounds (USs) for obstetrics residents, and abdominal ultrasonography by radiology trainees 10,13–17 . However, checklists are not widely utilized due partly to remaining gaps in the literature.…”
Section: Introductionmentioning
confidence: 99%